Ingestion of microplastics by copepods in Tampa Bay Estuary, FL - Fibbe, Mary Claire; Carroll, Delphine; Gowans, Shannon; Siuda, Amy N. S. (Frontiers in Ecology and Evolution, 2023)
Microplastics have been recognized as an emerging contaminant. Copepods are abundant primary consumers in marine food webs. Interactions between copepods and microplastics can lead to negative health effects to the individual and may have implications for populations and ecosystems through biomagnification. Laboratory and field studies have observed various species of zooplankton ingesting microplastics, however this is the first study to observe microplastic-copepod interactions in Tampa Bay. Over two years (November 2017 - January 2020), 14 sampling cruises were conducted with seven stations throughout Tampa Bay. At each station copepods were collected by towing a 200 µm mesh ring net (0.5 meter diameter) for 3 minutes. 1,000 individual Acartia tonsa copepods were picked from each sample and digested to release gut contents. Gut contents were stained in a Nile Red solution and then visualized using epifluorescent microscopy, quantified, photographed and sized using image analysis. In Tampa Bay, A. tonsa consumed fragments over fibers, ranging from 0.018 - 0.642 mm, with an average particle size of 0.076 mm. An overall average of 15.38 particles were ingested per 1,000 copepods, or 6.48 particles m-3 when normalized for environmental copepod concentrations. While significant differences were detected between stations and months, no clear spatial (from head to mouth of estuary) or temporal (between wet and dry seasons) trends in ingestion rate or ingested particle size were evident. These results show that A. tonsa ingested microplastics throughout Tampa Bay. These robust baseline data, for a copepod species that dominates estuarine zooplankton communities around the world, set the stage for valuable comparisons between estuaries with different physical mechanisms and levels of anthropogenic impact, allowing for exploration of how the environmental conditions impact ecological interactions.